AN ANALYSIS OF UNDERGRADUATE STUDENTS’ FORMAL ESSAY WRITING PERFORMANCE BASED ON HALLIDAY’ SYSTEMIC FUNCTIONAL LINGUISTICS THEORY - Ida Yulianawati; Natalia Anggrarini (JELLT (Journal of English Language and Language Teaching), 2022)
This study aims to analyze undergraduate students’ formal essay writing performance using Systemic Functional Linguistics theory. This study employed a qualitative research design, embracing the characteristics of a case study. The data were obtained from the collection of samples of students’ formal essay writing. The finding revealed that there were 192 clauses found in six undergraduate students’ formal essay writing and those clauses were analyzed in the three sections. They were transitivity process, mood, and theme. there was six transitivity process found in undergraduate students’ formal essay text. There were material prprocessesmental processes, relational processes, behavioral processes, verbal processes, and existential processes. The material process was used dominant by the students. There were three mood types found in the undergraduate students’ formal essay texts. The first was indicative declarative, the second was interrogative, and the last one was imperative. Drawing from the findings of mood, the declarative mood was the most dominant among the other two moods.